Comparative carbon and water footprint analysis and optimization of Organic Rankine Cycle. (25th July 2019) - Sun, Zhuang; Liu, Chao; Xu, Xiaoxiao; Li, Qibin; Wang, Xurong; Wang, Shukun; Chen, Xiaoxue
Highlights: Exergoenvironmental method-based models of carbon and water footprints of ORC system are established. Relationships between carbon and water footprints of ORC system are studied. Multi-objective optimization using genetic algorithm and grey relational analysis is conducted. Abstract: Carbon footprint (CF) and water footprint (WF) models are established based on exergoenvironmental method for Organic Rankine Cycle (ORC). Sensitivity study and multi-objective optimization are performed. R1233zd (E), R600a and R245fa and R245fa/R600a (0.5/0.5) are selected as the working fluids. The results show that the main methods to decrease CF and WF of ORC system are not the same from both exergoenvironmental analysis viewpoint and sensitivity study aspect. The differences lie in (i) from exergoenvironmental analysis viewpoint, reducing the CF cost of exergy destruction of evaporator and condenser is necessary; While reducing the WF costs rate of condenser is indispensable for WF reduction; (ii) regarding sensitivity study, the increase of evaporating temperature and decline of pinch point temperature difference in evaporator can be adopted to reduce the carbon emission; While increasing evaporating temperature and pinch point temperature difference in evaporator is effective to decrease the water consumption.